Comparison of Limberg Flap with Karydakis Repair in Pilonidal Sinus Disease (Medical Forum Monthly, 2024)
Objective: To compare Limberg flap with Karydakis repair in pilonidal sinus disease in terms of operative time and post-operative complications. Study Design: Randomized controlled trial. Place and Duration of Study: This study was conducted at the Department of General Surgery, Central Park Teaching Hospital, Lahore from July 2016 to June 2017. Materials and Methods: A total of 204 patients who underwent surgery for pilonidal sinus diseasewere included. Patients were randomly divided into two equal groups of n patients each by lottery method. Patients in Group L underwent surgery via the Limberg flap technique while patients in Group K were managed by the Karydakis repair technique. Both groups were then compared in terms of mean operative time, VAS pain score, postoperative complications and recurrence rates. Results: The mean operation time was 50.59±9.1 minutes in Group L versus 41.04±8.63 minutes in Group K, which was statistically significant (p˂0.001).The mean VAS pain score was 2.51±1.16 in Group L versus 3.19±1.45 in Group K, which was also statistically significant (p˂0.001). The difference in frequency of overall complications (p=0.391) and the recurrence rate (p=0.268) was statistically was non-significant. Conclusion: Karydakis repair is the better technique in terms of having lesser operation time and lesser frequency of wound dehiscence while Limberg flap technique is associated with lesser post-operative pain.